Socioeconomic inequalities in health-related fitness gradient shifts between 2001 and 2022 in young Polish adults - Domaradzki, Jarosław; Koźlenia, Dawid; Kochan-Jacheć, Katarzyna; Szkudlarek, Paweł; Fugiel, Jarosław (Frontiers in Public Health, 2023)
Background: This study aimed to assess the importance of socioeconomic status (SES) on health-related fitness (H-RF) measurements in young adults and determine the impact of SES over 20 years of substantial social and economic changes in Poland. Material & methods: The study compared H-RF differences between 2001 (P1) and 2022 (P2) in 252 volunteers aged 18 to 28, grouped into quartiles based on SES and gender. The variables measured included height, weight, body mass index, body fat mass, hand strength (hand grip), abdomen strength (sit-ups), flexibility (sit and reach), and leg power (standing long jump), with a synthetic motor performance index (MPSI) calculated for each participant. Results: Health-related differences based on social inequalities included body fat mass and MPSI, and two-way analysis of variance (ANOVA) revealed an interaction between SES and period on motor performance (F = 2.73, p = 0.045). In addition, post hoc tests revealed differences in P1 between SES quartiles one and two (p = 0.028). Over the last 20 years, physical fitness decreased, and body fat increased. The regression slope showed decreased motor performance with higher amounts of body fat in P2 subjects compared to their P1 peers. Conclusion: The observed trends may be associated with lifestyle changes shaped by technology development, high-energy and low-quality food access, and increased physical inactivity.